Immune biomarkers as an adjunct diagnostic modality of infection in cases of sudden and unexpected death in infancy (SUDI) at Tygerberg Medico-legal Mortuary, Cape Town, South Africa - Corena de Beer; Birhanu T Ayele; Johan Dempers (Elsevier, 2021)
Child mortality is a major health concern worldwide with over 4.2 million infants dying before reaching the age of one year in 2016 alone. Several international intervention initiatives have resulted in a decrease in the number of infant deaths; however, the incidence of sudden unexpected death in infancy (SUDI) and sudden infant death syndrome (SIDS) remain unacceptably high. SIDS still accounts for approximately 50-80% of SUDI cases, followed by infection.The aim of this study was to investigate a selection of immune biomarkers that are associated with an immune response in an effort to support the diagnosis of an infectious cause ("Infection") e.g. bronchopneumonia, interstitial pneumonitis, etc., instead of SIDS in SUDI cases. C-reactive protein and 18 different cytokines were retrospectively quantified in serum collected during post-mortem investigations of SUDI cases admitted to the Tygerberg Medico-legal Mortuary in the Western Cape Province of South Africa between 2015 and 2017. Statistical comparison was done between infants with a final cause of death (COD) of Infection and SIDS to investigate any correlations between the immune markers and sociodemographic information of the groups. A p-value of < 0.0026, after Bonferroni correction for multiple comparisons, was considered as statistically significant.A total of 169 cases were included, of which 65 (38.5%) were assigned a cause of death of Infection and 104 (61.5%) SIDS by forensic pathologists. The male to female ratio of the entire group was 1:0.97 and the median age at the time of death was 9 (interquartile range [IQR] 10.9) weeks. The majority (56.8%) of deaths occurred during the colder seasons (autumn and winter) and the median post-mortem interval was 4 (IQR 3) days.No statistically significant differences were demonstrated for gender, season, sleeping position or bed-sharing between the Infection and SIDS groups. Age and interleukin-1α were identified as predictors of a COD of Infection before adjusting for the multiple comparisons problem. C-reactive protein was a statistically significant predictor of a COD of Infection even after adjusting for the effect of multiple comparisons.The COD is primarily based on histopathology of the lungs, where other causes of interstitial inflammation have been ruled out, and where there are morphological changes present suggestive of infection, but not enough evidence to assign a final COD of Infection, the cases are concluded as SIDS. These biomarkers can therefore be valuable in the investigation protocol of SUDI cases to increase the number Infection cases where the histopathology of the lungs is suggestive of, but does not support conclusive evidence of infection.